Arrangements for radio-frequency heating of building structures. Issue 6 (5th November 2018) - Roland, Ulf; Holzer, Frank; Trommler, Ulf; Höhlig, Björn; Kraus, Markus; Hoyer, Christian
Abstract : Purpose: The aim of this study was to prove that radio-frequency (RF) energy with 13.56 MHz can be used for heating building structures in a controlled manner exploiting the advantage that homogeneous heating with sufficient penetration depths can be achieved. Design/methodology/approach: Because parallel electrodes on both sides of the heated structure cannot be used in many practical applications, two special electrode designs have been developed by modeling the field distribution and energy absorption and by carrying out test experiments to validate the simulation results. Findings: One solution is based on a two-dimensional surface capacitor providing certain penetration depths and being especially suitable for treating thin structures such as wooden parquet floor. Such an arrangement can be particularly used for pest control even when sensitive surfaces have to be protected. The other solution uses a capacitive coupling between the grounded shielding and an electrode or an equivalent structure (e.g. moist soil) at the other side of the masonry to establish a sufficiently strong electrical field between a "hot" electrode on the side of the shielding and the coupled rear electrode. Originality/value: Both solutions significantly enhance the application potential of RF heating.